A detailed investigation of the impact of online transportation on Bangladesh economy - Abbas Ali Khan; M. Raki Billah; Chandan Debnath; Sadekur Rahman; Md. Tarek Habib; Gazi Zahirul Islam (Institute of Advanced Engineering and Science, 2019)
Transportation is one of the main part of our daily life especially in Dhaka City where traffic jam, security, harassment of fare and other problems are big issue at conventional vehicle. A couple of year ago since 2016 the online maintain vehicle has introduced by “Pathao” and “Ubar” both have car and motor cycle ride share. The main purpose of this paper is to focus the facilities of IT on transport basis of security, transparent cash-on-delivery, hassle-free communication, reduce waiting time for the passenger and the impact of IT on Bangladesh economy.